Glutathione Supplementation Reduces MMP-9 Levels and Infarct Area in Rats Models of Acute Ischemic Stroke - Anam, Churriyyatul; Retnaningsih; Suci, Nyoman (Pakistan Journal of Nutrition, 2018)
Background and Objective: Ischemic stroke occurs when blood vessels vascularizing the brain are blocked and unable to receive oxygen or glucose. Matrix metalloproteinases (MMPs) have been implicated in the pathophysiology of stroke. MMP-9 is known as an early marker related to incidence of stroke. While standard therapy for stroke is unable to repair damaged brain tissues, glutathione (GSH) inhibits oxidative stress activity and reduces excess MMP-9 levels in order to avoid pathological angiogenesis in ischemic stroke. This study was conducted to demonstrate the effect of GSH on MMP-9 levels and infarcted areas after acute ischemic stroke compared with standard therapy. Methods: This experimental study used a post-test only control group design. Twenty male Wistar rats were equally divided into 4 groups and orally treated with placebo, 0.72 mg aspirin/100 g body weight, 21.6 mg GSH/100 g body weight or GSH+aspirin for 7 day following induction of ischemic stroke by unilateral cerebral artery occlusion. Serum MMP-9 levels were measured by ELISA and infarct size (area) was measured by cresyl violet staining. Results: Both MMP-9 levels and infarct area were significantly reduced (p<0.05) in all treatment groups versus control group (placebo). GSH+aspirin therapy showed the greatest reductions. Conclusion: Combining GSH and aspirin significantly decreased MMP-9 levels and infarct area after acute ischemic stroke compared to standard therapy alone.